ESIF policies and their impact on the development of EU members: A review and research agenda - Nishimura, A. Z. F. C.; Au-Yong-Oliveira, M.; Sousa, M. (Quality - Access to Success, 2021)
The European Structural and Investment Funds (ESIF) represent the main instrument of European Cohesion Policy to sustain territorial development and to eliminate regional disparities between the EU member states. The study of the impacts of ESIF on the economic growth and development of EU members has gained increasing attention in the academic community, and there has been significant scientific production on this topic. This study consists of a bibliometric analysis of articles published in the period from 2011 to 2020 and indexed in two of the main scientific databases: Web of Science (WoS) and Scopus. The results of the bibliometric analysis point to relevant trends on the subject, such as the growing number of publications over the years; the great concentration of studies applied in Central and Eastern European (CEE) countries, namely Romania; and the current interest of researchers in important topics associated with European funds, such as the competitiveness and innovation of SMEs, climate change, economic impact of global crises, sustainable development, institutional capacity of organisations, and cross-border cooperation